2024
DOI: 10.3390/en17030752
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art and Environmental Aspects of Plant Microbial Fuel Cells’ Application

Roman Lepikash,
Daria Lavrova,
Devard Stom
et al.

Abstract: Environmental pollution is becoming ubiquitous; it has a negative impact on ecosystem diversity and worsens the quality of human life. This review discusses the possibility of applying the plant microbial fuel cells (PMFCs) technology for concurrent processes of electricity generation and the purification of water and soil ecosystems from organic pollutants, particularly from synthetic surfactants and heavy metals. The review describes PMFCs’ functioning mechanisms and highlights the issues of PMFCs’ environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 179 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…It can be seen that the MFC-Target managed to reduce the concentration of As, Cu, and Fe by 90.83, 14.53, and 84.625%, while the MFC-P. stutzeri reduced As, Cu, and Fe by 90.83, 25.377, and 89.73%, respectively, in 72 h. The decrease in the values of these metals may be due to a series of natural phenomena that occur within the MFC, for example, the adhesion of these metals to the anode electrode (activated carbon) due to the porosity that this electrode presents in addition to the same metabolic activity of microorganisms that can convert these metals into non-toxic compounds [44,45]. It has also been observed in previous works that the increase in arsenic concentrations significantly decreases the energy values, because it results in a toxic substance for the electrogenic microorganisms in the anodic chambers [46], but in this research, we worked with values found in the studied river. The decrease in energy values can also be explained because the toxic arsenic, iron, and copper attached to the electrode had enough time to diffuse into the biofilm, directly affecting the cells and inhibiting the activity of bacteria [47,48].…”
Section: Results and Analysismentioning
confidence: 97%
“…It can be seen that the MFC-Target managed to reduce the concentration of As, Cu, and Fe by 90.83, 14.53, and 84.625%, while the MFC-P. stutzeri reduced As, Cu, and Fe by 90.83, 25.377, and 89.73%, respectively, in 72 h. The decrease in the values of these metals may be due to a series of natural phenomena that occur within the MFC, for example, the adhesion of these metals to the anode electrode (activated carbon) due to the porosity that this electrode presents in addition to the same metabolic activity of microorganisms that can convert these metals into non-toxic compounds [44,45]. It has also been observed in previous works that the increase in arsenic concentrations significantly decreases the energy values, because it results in a toxic substance for the electrogenic microorganisms in the anodic chambers [46], but in this research, we worked with values found in the studied river. The decrease in energy values can also be explained because the toxic arsenic, iron, and copper attached to the electrode had enough time to diffuse into the biofilm, directly affecting the cells and inhibiting the activity of bacteria [47,48].…”
Section: Results and Analysismentioning
confidence: 97%